Storytelling and User-Generated Content as Marketing Communication Strategies: A Case Study of @beranibackpacker on Instagram - Rofian Dedi Susanto; Rifky Maulana (UIN Fatmawati Sukarno Bengkulu, 2026)
The rapid advancement of digital technology has fundamentally transformed the tourism marketing landscape, shifting paradigms from unilateral broadcasting toward participatory co-creation. To facilitate this, integrating digital storytelling and User-Generated Content (UGC) has become a crucial mechanism for cultivating authentic interactions, a practice notably demonstrated by the travel community Berani Backpacker. Consequently, this study examines the application of these dual instruments as a cohesive marketing communication strategy on Instagram. Moving beyond conventional itinerary promotion, this research explores how the operator commodifies the content creation process through a